Un’esperienza clinica di psicoterapia di gruppo in un dipartimento di salute mentale - Pomepi, Roberta; Giampà, Alessio (Il sogno della farfalla, 2020)
This article analyses the role of public mental health services in Italy. The authors firstly highlight how since recent years psychotherapy is one of the treatment that the government has to guarantee to its citizens. The history of the establishment of current public psychiatric ambulatory CSM (Mental health service) is then briefly analysed. In this paper a particular focus is given to two groups of psychotherapy held in a CSM. The authors explains that in this clinical practice, based on the Human Birth Theory formulated by Massimo Fagioli, frustration is considered as a fundamental therapeutic factor.